Peaceful uses of outer space under threat? Evaluating the international legal framework regulating space activities amidst increased militarisation and weaponisation - Paramonova-Izugbaja, Marina (Riga Graduate School of Law, 2024)
Outer space is playing an increasingly important role in modern life, from everyday activities to critical technological advancements. However, there are concerns that it is also becoming progressively more congested, contested, and competitive, prompting fears that its historically peaceful applications may be jeopardised. Increased competitiveness in space comes against the backdrop of growing geopolitical tensions and an increase in the level of conflict around the world, leading many observers to suggest that outer space might become the next theatre of war. This thesis seeks to assess whether the current international legal framework adequately regulates the increasing militarisation and weaponisation of outer space which in turn might lead to space warfare. To achieve its objectives, the study closely examines the concepts of “militarisation”, “weaponisation” and “space warfare”, inspects the broader international space law and critically assesses various binding and non-binding instruments of potential relevance to the regulation of militarisation and weaponisation of space – such as the Outer Space Treaty, the Charter of the United Nations, key General Assembly resolutions, and others. Based on the analysis, the thesis concludes that the current legal framework is outdated and insufficient to address contemporary challenges. It advocates for updating the existing agreements or developing new binding agreement(s) focused specifically on maintaining peace in outer space through regulating its increased militarisation and weaponisation.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; Space law; space warfare